Day 2 Wed, April 19, 2017 2017
DOI: 10.2118/184414-ms
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Produced Gas for Improved Oil Recovery and Reduced Emissions from the Bakken Formation

Abstract: Oil production grew significantly from 0.2 million barrels per day (bpd) to 1.1 million bpd in the Bakken petroleum system from 2009 to 2014. A large volume of associated gas (1.6 billion cubic feet per day) has also been produced with the oil. A substantial part (>10%) of this produced gas is flared off because of the low natural gas price and limited infrastructure for gathering and transporting the gas from the well sites. Such a large scale of gas flaring not only wastes energy but also emits contam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 23 publications
0
29
0
Order By: Relevance
“…Water floods, commonly being used in conventional reservoirs as an improved oil recovery (IOR) method, has been proven to be unfeasible in tight unconventional shale formations [17,27]. In the past decade, gas injection, including huff-n-puff injection or cyclic gas injection, and gas flooding, has been demonstrated to be a promising EOR method for shale reservoirs and has been extensively studied in oil and gas research laboratories and widely modeled through numerical simulation methods by many researchers [8][9][10][11][12]14,16,17]. We review the recent research progress on gas injection in shale oil reservoirs through huff-n-puff (Section 2.1.1) and gas flooding (Section 2.1.2) methods and summarize the gas injection mechanisms in Section 2.1.3.…”
Section: Enhanced Oil Recovery Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Water floods, commonly being used in conventional reservoirs as an improved oil recovery (IOR) method, has been proven to be unfeasible in tight unconventional shale formations [17,27]. In the past decade, gas injection, including huff-n-puff injection or cyclic gas injection, and gas flooding, has been demonstrated to be a promising EOR method for shale reservoirs and has been extensively studied in oil and gas research laboratories and widely modeled through numerical simulation methods by many researchers [8][9][10][11][12]14,16,17]. We review the recent research progress on gas injection in shale oil reservoirs through huff-n-puff (Section 2.1.1) and gas flooding (Section 2.1.2) methods and summarize the gas injection mechanisms in Section 2.1.3.…”
Section: Enhanced Oil Recovery Methodsmentioning
confidence: 99%
“…In a similar study, Zhang et al [52] calculated MMPs for CO 2 floods in Bakken and concluded that the MMP was reduced by 5% due to the confinement effects of nanopores, including both large capillary pressures and the shift in critical properties. It should be noted that in this study and another similar study [10], the MMP was measured by using the vanishing interfacial tension (VIT) method, which has been shown to have significant limitations even for conventional reservoirs [53]. Nojabaei and Johns [54] studied the effect of large gas-oil capillary pressure on fluid properties and saturation pressures when the produced gas was injected to enhance oil recovery.…”
Section: Sensitivity Analysismentioning
confidence: 98%
See 3 more Smart Citations